COMPARATIVE STUDY OF DESCRIPTORS FOR MEDICAL IMAGE RETRIEVAL - А. А. Dmitruk (Informatika)
This paper presents results of comparative analysis of image descriptors in the context of content- based medical image retrieval problem. Experiments are carried out on 11 test databases using 137 different types of descriptors. Image descriptors based on co-occurrence matrices and local binary patterns showed the best performance.